Prix de la Jeune Peinture Belge : 1997. - Cohen, Lynne; Gillion, Roland; Pirotte, Philippe; Van Tieghem, Jean-Pierre; Paleis voor Schone Kunsten Brussel (Brussel : Paleis voor Schone Kunsten Brussel, 1997)
Boelens, Peter ; De Boer, Manon-S. ; Boessen, Judith ; Cereghetti, Caroline ; Claerbout, David ; Danckaert, Bert ; Geyskens, Vincent ; Gillen, Tina ; Meyers, Koen ; Opsomer, Els ; Roussel, Benoît ; Vanhoe, Reinaart ; Vranken, Dominique
Quelque point de repère = Enkele belangrijke data p. 10, 11
biog., tent. p. 50-55
Engels
Frans
Frans & Nederlands
Nederlands